TECHNOLOGY OF PHOTOSENSITIVE THIN-FILM STRUCTURES CdSe, CdSe:Cd,Cl, CdSe:Cu,Cl WITH LONGITUDINAL PHOTOCONDUCTIVITY - Yuldashev Norsirjon Khaydarovich; Ayibjanov Mukhta; Tuychibayev Bakhodir Kurbonaliyevich (Web of Journals Publishing, 2025)
A method for fabricating longitudinally operating cadmium selenide photosensitive films and transparent conductive contacts on SnO2 and CdO is presented. It is shown that photosensitive films with stable and reproducible electrophysical characteristics are obtained using annealing temperatures in air in the presence of CdCl2 of -470°C; and CuCl2 of -300°C.
Keywords: photosensitive film, CdSe, CdSe:Cd,Cl, CdSe:Cu,Cl, longitudinal photoconductivity, transparent contacts, heat treatment, sensitization kinetics, SnO2 and CdO.